2024
DOI: 10.3390/antibiotics13010102
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Antibiotic Consumption before and during the COVID-19 Pandemic in Hungary

Roxána Ruzsa,
Ria Benkő,
Helga Hambalek
et al.

Abstract: The aim of this study was to assess antibiotic use in the Hungarian hospital care sector during and before the pandemic. Aggregated systemic antibiotic (ATC: J01) utilisation data were obtained for the 2010–2021 period. Classifications and calculations were performed according to the WHO ATC/DDD index and expressed as DDD per 1000 inhabitants and per day (DID), DDD per 100 patient-days (DHPD) and DDD/discharge. A linear regression (trend analysis) was performed for the pre-COVID years (2010–2019) and a predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A retrospective drug-utilization study in Campania, southwestern Italy, found a higher prevalence of this third-generation cephalosporins (ATC J01DD) in COVID-19 positive adults under 40 and above 80, compared to the general population [ 32 ]. Additionally, a Hungarian study on hospital antibiotic consumption revealed a noteworthy 63.7% increase in the utilization of ATC J01DD from 2010 to 2019, with a substantial 70.46% surge during the pandemic years from 2019 to 2020 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective drug-utilization study in Campania, southwestern Italy, found a higher prevalence of this third-generation cephalosporins (ATC J01DD) in COVID-19 positive adults under 40 and above 80, compared to the general population [ 32 ]. Additionally, a Hungarian study on hospital antibiotic consumption revealed a noteworthy 63.7% increase in the utilization of ATC J01DD from 2010 to 2019, with a substantial 70.46% surge during the pandemic years from 2019 to 2020 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%